The art of the steal [videorecording (DVD)] - Argott, Don; Argott, Don (IFC in Theaters : MPI Media Group, 2010)
It's been called the greatest theft of art since the Second World War. Reveals how a private collection of paintings became the envy of the Louvre, the Metropolitan Museum of Art, and other major institutions, and the prize in a battle between one man's vision and the forces of commerce and politics. Founded in 1922 by wealthy American drug developer and art collector Albert C. Barnes, the Barnes Foundation became the finest collection of paintings by Renoir, Cezanne, Matisse, and Van Gogh.